Pemberdayaan Pokdarwis Kampung Parakanceuri: Membangun Sumber Daya Manusia Sadar Wisata dan Tanggap Bencana - Fajar Aditya Nugroho; Sabrina Azzahra; Rezka Fedrina; Alayya Fildzah Farhana (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Kampung Parakanceuri Tourism Village possesses significant natural tourism potential but faces risks of landslides and flash floods. Despite their strategic role, the human resource capacity of the Tourism Awareness Group (Pokdarwis) in disaster mitigation remains limited due to committee regeneration and a false sense of security since the 2009 disaster. This community service project aims to enhance Pokdarwis' capacity through a Service Learning (SL) approach involving investigation, preparation, action, and reflection stages. The results indicate an improvement in partners' understanding, evidenced by the collaborative development of disaster Standard Operating Procedures (SOPs) and the installation of educational posters at vulnerable points. However, a significant challenge remains in the form of a strong "fatalism" principle, leading to the neglect of financial protection like insurance and professional certification. This program suggests strengthening preparedness through formalized insurance partnerships and certified mitigation training to ensure sustainable destination safety.